ISLAM: AGAMA ANTI KEKERASAN - Yuwono, Yohanes H. (UNIKA Santo Thomas, 2002)
No single of the revealed religions nor Islam, encourages or teachesviolence to its believers. Islam which is based on the Qur’an as its HolyScripture summons its faithfuls to spread peace, harmony and socialwelfare. It is true that we find several verses that encourage war, but jihadin the sense of holy war in Islam is the last way of a self defense after allgood manner of dialogs fail to bear fruits of understanding. In these sensejihad could be done because the truth must stand firm before evil.